STEM-Based Straight Motion Learning to Improve Creative Thinking Skills STEM-Based Straight Motion Learning to Improve Creative Thinking Skills for Class VIII Students - Wahyu Hidayat; Gusniwati Gusniwati; Hardiana Hardiana (Universitas Muhammadiyah Enrekang, 2022)
The ability to think creatively is one aspect that plays an important role in preparing students to face the challenges of modern times. The purpose of this study was to describe learning in straight motion with a STEM approach that could improve students' creative thinking skills. This research is a Classroom Action Research (CAR). The data analysis technique used is quantitative analysis technique to analyze the assessment score and qualitative analysis technique to summarize and describe the research results through observational observations. The results showed that in the learning process students were quite enthusiastic in expressing their opinions and students were also quite creative in each indicator of creative thinking. In addition, it is seen based on test scores and student reports. For the percentage of students whose scores are above the KKM in the first cycle, it reaches 56.25% on the test. However, if it is seen in the report, it reaches 50%, so it has not reached the criteria for research success. In the second cycle, improvements will be made in the first cycle so that the percentage of students' scores above the KKM in the second cycle will increase. On the test it increased to 93.75% and on the report it increased to 81.25%. Based on research results and reviews, it can be said that STEM-based straight motion learning at UPT SMP Negeri 3 Pangsid can improve students' creative thinking skills.